Distributed generation systems design, operation and grid integration - Gharehpetian, G. B.; Mousavi Agah, S. Mohammad (Oxford, United Kingdom Butterworth-Heinemann, 2017)
Distributed Generation Systems: Design, Operation and Grid Integration closes the information gap between recent research on distributed generation and industrial plants, and provides solutions to their practical problems and limitations. It provides a clear picture of operation principles of distributed generation units, not only focusing on the power system perspective but targeting a specific need of the research community. This book is a useful reference for practitioners, featuring worked examples and figures on principal types of distributed generation with an emphasis on real-world examples, simulations, and illustrations. The book uses practical exercises relating to the concepts of operating and integrating DG units to distribution networks, and helps engineers accurately design systems and reduce maintenance costs.--Provided by publisher.
Distributed energy resources / Mehrdad Mokhtari, G.B. Gharehpetian, S. Mohammad Mousavi Agah -- The basic principles of wind farms / Ahmed Rashad, Salah Kamel, Francisco Jurado -- Solar energy and photovoltaic technology / Kakkan Ramalingam, Chandrasen Indulkar -- Microturbine generation power systems / R. Noroozian, P. Asgharian -- Fuel cells / Hamdi Abdi, Ramtin Rasouli Nezhad, Mohammad Salehimaleh -- Design of small hydro generation systems / Morteza Nazari-heris, Behnam Mohammadi-Ivatloo -- Energy storage systems / Hamdi Abdi, Behnam Mohammadi-ivatloo, Saeid Javadi, Amir Reza Khodaei, Ehsan Dehnavi -- Market design issues of distributed generation / Jeremy Lin, Fernando H. Magnago, Elham Foruzan, Ricardo Albarracín-Sánchez -- Distribution generation optimization and energy management / Barry Hayes -- Impact of distributed generation integration on the reliability of power distribution systems / Mohammad AlMuhaini -- DC distribution networks: A solution for integratin of distributed generation systems / Mehdi Monadi, Kumars Rouzbehi, Jose Ignacio Candela, Pedro Rodriguez.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Distributed generation of electric power; Small power production facilities -- Design and construction; Electronic books